CMTM3 regulates vascular endothelial cell dysfunction by influencing pulmonary vascular endothelial permeability and inflammation in ARDS - Xiao, Ziyan; Zhou, Gang; Xue, Haiyan; Chen, Lihe; Zhao, Xiujuan; Li, Shu; Fu, Chun; Wang, Zhengzhou; Zhu, Fengxue (Frontiers in Immunology, 2025)
IntroductionCMTM3 is a member of the human chemokine-like factor superfamily. The mechanistic role of CMTM3 in acute respiratory distress syndrome (ARDS) is not known. This study investigated the role of CMTM3 in the progression of ARDS and its impact on the function of vascular endothelial cells.MethodsARDS modeling in human umbilical vascular endothelial cells (HUVECs) was performed by treating with lipopolysaccharide (LPS) or hypoxia/reoxygenation. We assessed CMTM3 expression levels in the LPS- and hypoxia/reoxygenation-stimulated HUVEC cells. Furthermore, we assessed the role of CMTM3 in the permeability function and inflammatory response of the vascular endothelial cells under ARDS conditions using HUVEC cells with CMTM3 overexpression(adCMTM3) or knockdown(shCMTM3). Concurrently, we generated CMTM3 knockout (CMTM3ko) mice and evaluated the differences in pulmonary vascular permeability, inflammatory lung injury, and survival rates between the CMTM3ko-ARDS and WT-ARDS model mice.ResultsHUVECs stimulated with LPS and hypoxia/reoxygenation showed significantly higher CMTM3 expression compared to the control group (p<0.05). Compared with the adsham-HUVECs, adCMTM3-HUVECs stimulated with LPS and hypoxia/reoxygenation demonstrated significantly higher cellular permeability (p<0.05) as well as IL-6 and TNF-α expression levels (p<0.05). Conversely, shCMTM3-HUVECs stimulated with LPS and hypoxia/reoxygenation showed significantly reduced cellular permeability as well as IL-6 and TNF-α expression levels (p<0.05). In vivo ARDS modeling experiments demonstrated that CMTM3-knockout ARDS mice exhibited significantly higher survival rates (p=0.0194) as well as significantly reduced lung injury and pulmonary vascular permeability (p<0.05) compared to the wild-type ARDS mice. DiscussionThese findings demonstrated that CMTM3 played a critical role in the development of ARDS by influencing permeability of the pulmonary vascular endothelial cells and lung inflammation. Therefore, CMTM3 is a potential therapeutic target in ARDS.